COVID-19 pandemic and weight gain in American adults: A nationwide population-based study. Issue 1 (January 2022) - Khubchandani, Jagdish; Price, James H.; Sharma, Sushil; Wiblishauser, Michael J.; Webb, Fern J.
Abstract: Background: The COVID-19 pandemic has affected the lives of people in many ways. However, little is known about weight gain in American adults during the pandemic. Aims and methods: The purpose of this study was to conduct a national assessment of weight gain in adult Americans after the first year of the pandemic. An online questionnaire was employed to explore perceptions of adults regarding pandemic weight gain and the relationship between weight gain and sociodemographic characteristics, pre-pandemic weight status, and psychological distress. Multiple methods were used to assess the psychometric properties of the questionnaire (i.e., face validity, content validity, and internal consistency reliability testing). Chi-Square tests and logistic regression analysis were used to assess group differences and predictors of weight gain in the study participants. Results: A total of 3, 473 individuals participated in the study with weight changes distributed as: gained weight (48%), remained the same weight (34%), or lost weight (18%). Those who reported being very overweight before the pandemic were most likely to gain weight (65%) versus those who reported being slightly overweight (58%) or normal weight (40%) before the pandemic. Weight gain was statistically significantly higher in those with anxiety (53%), depression (52%), or symptoms of both (52%). The final multiple regression model found that the statistically significant predictors of pandemic weight gain were psychological distress, pre-pandemic weight status, having children at home; and time since last bodyweight check. Conclusions: Population health promotion strategies in the pandemic should emphasize stress reduction to help individuals manage body weight and avoid chronic diseases in the future. Highlights: Nearly half (48%) of the adult Americans gained weight during the pandemic. Those who were overweight before the pandemic were most likely to gain weight. Depression and anxiety symptoms were strong predictors of weight gain in pandemic. Time since last weight check and children at home were related to excess weight gain.